Dealkylation metabolites of Atrazine: A previously Neglected Contributor to soybean phytotoxicity within atrazine residue - Nan Wang; Yabo Liang; Wangjing Zhai; Fanrong Zhao; Li Zheng; Peng Wang; Zhiqiang Zhou; Xueke Liu; Donghui Liu (Environment International)
The phytotoxicity risks of atrazine to crops have received widespread attention, but the toxic effects of its metabolites on plants have been largely overlooked. In this study, the contributions and mechanisms underlying phytotoxicity of the atrazine and its metabolites (DEA and DIA) were systematically investigated in soybean seedlings. Two dealkylation metabolites DEA and DIA caused growth suppression, inhibited photosynthesis, activated the antioxidant system, and induced changes in chloroplast ultrastructure in soybean seedlings. Integrated Biological Response (IBR) analysis indicated that at equivalent environmentally relevant concentrations, the toxicity indices of DEA and DIA were 73.60% and 34.00% of atrazine, respectively. Molecular docking analysis revealed that both DEA and DIA exhibited high binding energies with Photosystem II D1 protein, with their potential target protein in soybean plants being consistent with that of atrazine. Metabolomic analysis further confirmed that the metabolites DEA and DIA disrupt key metabolic pathways, including alpha-linolenic acid metabolism, consistent with the mode of action of atrazine. These effects are associated with the inhibition of the photosynthetic electron transport chain and ROS accumulation. By calculating the environmental risk quotient, the risk of metabolites DEA to succeeding crops is likely to exceed that posed by the parent atrazine. These findings suggested that dealkylation metabolites of atrazine are overlooked contributors to soybean phytotoxicity in atrazine residue, and the risks posed by herbicide metabolites to crops need to be addressed.